A Comparative Analysis of Non-Routine Problems in Mathematics Textbooks of Indonesia and Singapore - Manopo Manopo; Varetha Lisarani (Edumatika : Jurnal Riset Pendidikan Matematika, 2021)
Textbooks used in schools affect the quality of mathematics learning in the country. Indonesian Ministry of Education (Kemendikbud) already lauched students’ and teachers’ textbook that are distributed nationally on 2013; however improvements are needed to revise the textbooks since there are concerns such as the difficulty level of problems contained in the textbooks. The main objective of this study is to compare non-routine problems contained in mathematics textbooks used in Indonesia and Singapore. This is a qualitative research with content analysis design. Researchers compare Singaporean and Indonesian mathematics textbook since Singapore got higher rank in mathematics based on PISA result in 2018. The topic in this study is limited to Pythagorean Theorem. The result of the research shows that Indonesia and Singapore has consecutively 22,1% and 11,3% non-routine problem. Another finding of this study was Singaporean mathematics textbook focused more on developing students’ fluency of solving problems, meanwhile Indonesian mathematics textbook focused more on students’ reasoning ability. The results and findings in this paper are expected to provide input in developing future mathematics textbooks.